Measurement of hemorrhage-related severe maternal morbidity with billing versus electronic medical record data. (18th June 2022) - Friedman, Alexander M.; Oberhardt, Matthew; Sheen, Jean-Ju; Kessler, Alan; Vawdrey, David; Green, Robert; D'Alton, Mary E.; Goffman, Dena
Abstract: Objective: Measurement of obstetric hemorrhage-related morbidity is important for quality assurance purposes but presents logistical challenges in large populations. Billing codes are typically used to track severe maternal morbidity but may be of suboptimal validity. The objective of this study was to evaluate the validity of billing code diagnoses for hemorrhage-related morbidity compared to data obtained from the electronic medical record. Study design: Deliveries occurring between July 2014 and July 2017 from three hospitals within a single system were analyzed. Three outcomes related to obstetric hemorrhage that are part of the Centers for Disease Control and Prevention definition of severe maternal morbidity (SMM) were evaluated: (i) transfusion, (ii) disseminated intravascular coagulation (DIC), and (iii) acute renal failure (ARF). ICD-9-CM and ICD-10-CM for these conditions were ascertained and compared to blood bank records and laboratory values. Sensitivity, specificity, positive (PPV) and negative predictive values (NPV) with 95% confidence intervals (CI) were calculated. Ancillary analyses were performed comparing codes and outcomes between hospitals and comparing ICD-9-CM to ICD-10-CM codes. Comparisons of categorical variables were performed with the chi-squared test. T-tests were used to compare continuous outcomes. Results: 35, 518 deliveries were analyzed. 786 women underwent transfusion, 168 had serum creatinine ≥1.2 mg/dL, and 99, 40, and 16 had fibrinogen ≤200, ≤150, and ≤100 mg/dL, respectively. Transfusion codes were 65% sensitive (95% CI 62–69%) with a 91% PPV (89–94%) for blood bank records of transfusion. DIC codes were 22% sensitive (95% CI 15–32%) for a fibrinogen cutoff of ≤200 mg/dL with 15% PPV (95% CI 10–22%). Sensitivity for ARF was 33% (95% CI 26–41%) for a creatinine of 1.2 mg/dL with a PPV of 63% (95% CI 52–73%). Sensitivity of ICD-9-CM for transfusion was significantly higher than ICD-10-CM (81%, 95% CI 76–86% versus 56%, 95% CI 51–60%, p < .01). Evaluating sensitivity of codes by individual hospitals, sensitivity of diagnosis codes for transfusion varied significantly (Hospital A 47%, 95% CI 36–58% versus Hospital B 63%, 95% CI 58–67% versus Hospital C 80%, 95% CI 74–86%, p < .01). Conclusion: Use of administrative billing codes for postpartum hemorrhage complications may be appropriate for measuring trends related to disease burden and resource utilization, particularly in the case of transfusion, but may be suboptimal for measuring clinical outcomes within and between hospitals.